PENERAPAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA MTs HASYIM ASYARI AMBON PADA MATERI POKOK ENERGI DALAM KEHIDUPAN - Hamida, Wa Ode; Natsir, Nur Alim; Hardiansyah, Muhammad Rizal; Mursalin, Enggal (LP2M IAIN Ambon, 2024)
This study aims to increase the interest and learning outcomes of MTs Hasyim Asy'ari Ambon students in the subject matter of energy in living systems by using audio-visual media as learning media. This research is an classroom action research. The findings show that students' interest and learning outcomes increase after using audio-visual media. This increase can be seen from the results of observations, questionnaires, and formative tests in cycle I. That is, students' learning interest in cycle I is based on observations, classically 54.2%, and based on classical questionnaires 54.8% for formative test results in cycle I classically of 54.2%, while the results of observations, questionnaires and formative tests in cycle II were 84% for observation of interest in learning, 86.2% for interest questionnaires and 88.5% for formative test results. Based on this analysis it was concluded that the application of audio-visual media can increase the interest and learning outcomes of MTs Hasyim Asy'ari Ambon students in the subject matter of energy in living systems.